Reporting data on implementation of nutrition education using the Community Health Promoters’ cascade model in urban informal settlements in Kisumu (2023-2025) - Musita, Consolata Nolega; Juliane Podlech; Akingbemisilu, Tosin Harold; Jordan, Irmgard; Termote, Celine (2025)
This data was collected through the HealthyFoodAfrica Project (https://healthyfoodafrica.eu/), a research and innovation initiative aimed at improving nutrition in Africa by enhancing the diversity, sustainability, resilience, and connectivity of food systems. The project seeks to effectively reconnect food production and consumption. It was implemented in 10 cities across six African countries.